Autophagy Protects From Uremic Vascular Media Calcification - Frauscher, Bianca; Kirsch, Alexander H.; Schabhüttl, Corinna; Schweighofer, Kerstin; Kétszeri, Máté; Pollheimer, Marion; Dragun, Duska; Schröder, Katrin; Rosenkranz, Alexander R.; Eller, Kathrin; Eller, Philipp (Frontiers in Immunology, 2018)
Chronic kidney disease and diabetes mellitus are associated with extensive media calcification, which leads to increased cardiovascular morbidity and mortality. Here, we investigated the role of autophagy in the pathogenesis of uremic vascular media calcification. DBA/2 mice were fed with high phosphate diet (HPD) in order to cause vascular calcification. DBA/2 mice on standard chow diet (SCD) were used as control. In parallel, autophagy and its response to rapamycin, 3-methyladenine and bafilomycin were also studied in an in vitro model using mouse vascular smooth muscle cells (MOVAS). DBA/2 mice on HPD developed severe vascular media calcification, which is mirrored in vitro by culturing MOVAS under calcifying conditions. Both, in vitro and in vivo, autophagy significantly increased in MOVAS under calcifying conditions and in aortas of HPD mice, respectively. Histologically, autophagy was located to the aortic tunica media, but also vascular endothelial cells, and was found to continuously increase during HPD treatment. 3-methyladenine as well as bafilomycin blocked autophagy in MOVAS and increased calcification. Vice versa, rapamycin treatment further increased autophagy and resulted in a significant decrease of vascular calcification in vitro and in vivo. Rapamycin reduced Runx2 transcription levels in aortas and MOVAS to control levels, whereas it increased α-smooth muscle actin (SMA) and Sm22α transcription in MOVAS to control levels. Furthermore, rapamycin-treated HPD mice survived significantly longer compared to HPD controls. These findings indicate that autophagy is an endogenous response of vascular smooth muscle cells to protect from calcification in uremia. Induction of autophagy by rapamycin protects cells and mice from uremic media calcification possibly by inhibiting osteogenic transdifferentiation of vascular smooth muscle cells.